2021
DOI: 10.1038/s41467-021-23944-w
|View full text |Cite
|
Sign up to set email alerts
|

Cu2Se-based thermoelectric cellular architectures for efficient and durable power generation

Abstract: Thermoelectric power generation offers a promising way to recover waste heat. The geometrical design of thermoelectric legs in modules is important to ensure sustainable power generation but cannot be easily achieved by traditional fabrication processes. Herein, we propose the design of cellular thermoelectric architectures for efficient and durable power generation, realized by the extrusion-based 3D printing process of Cu2Se thermoelectric materials. We design the optimum aspect ratio of a cuboid thermoelect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 67 publications
1
55
1
Order By: Relevance
“…Direct ink writing (DIW), a type of extrusion 3D printing technology, has recently emerged as a convenient and low-cost method of constructing custom-built shapes. [14][15][16] To date, many TE materials and devices including conducting polymers, 17,18 Bi 2 Te 3 -based, 13,19 PbTe-based, 20 and Cu 2 Se-based 21 compounds can be printed. Nevertheless, the ZT values of 3D-printed materials are lower than those of bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct ink writing (DIW), a type of extrusion 3D printing technology, has recently emerged as a convenient and low-cost method of constructing custom-built shapes. [14][15][16] To date, many TE materials and devices including conducting polymers, 17,18 Bi 2 Te 3 -based, 13,19 PbTe-based, 20 and Cu 2 Se-based 21 compounds can be printed. Nevertheless, the ZT values of 3D-printed materials are lower than those of bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Furthermore, the pores created from the pressureless sintering process also hinder the transportation of electrons. 13,20,21,27 Therefore, organic residuals and porosities are the longstanding challenges in ZT enhancement, which so far has not been achieved in DIWed TE materials.…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2 Se powder was synthesised by the high-energy ball-milling of Cu and Se powders (2:1, atomic ratio) for 200 min as described in a previous report 25 . Ball-milled Cu 2 Se powder (103 mg) was added to a mixture of 1 ml of ethylenediamine and 0.1 ml of ethanedithiol (10:1, v/v) in a 10 ml vial with a stirring bar.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 However, the toxicity of Te has resulted in the promotion of studies on comparatively less toxic and earthabundant Se-based materials with similar properties. 14 Accordingly, various studies have been conducted to improve the thermoelectric performance of Bi 2 Se 3 -, [15][16][17] Bi 2 O 2 Se-, 18,19 Cu 2 Se-, [20][21][22] SnSe [23][24][25] and Cu 7 Sn 3 S 10 -based materials. 26,27 Further, recent studies have demonstrated the synthesis of complex derivative compounds with a series of primitive cells based on Groups II-VI compounds, such as ternary I-III-VI, II-IV-V, II-III-VI, I-IV-VI, I-V-VI, and quaternary I-II-IV-VI compounds.…”
Section: Introductionmentioning
confidence: 99%